초음파와 베이킹 소다 처리가 채소 유기종자 소독과 발아율에 미치는 영향 - 김민정(Min-Jeong Kim); 심창기(Chang-Ki Shim); 김주(Ju Kim); 고병구(Byong-Gu Ko) (Weon'ye gwahag gi'sulji, 2020)
본 연구에서는 2% 베이킹 소다와 초음파의 단독 및 혼합 처리가 근채류, 엽채류, 과채류 유기종자의 곰팡이와 세균의 소독 효과와 발아율에 미치는 영향을 검정하고자 하였다. 근채류, 엽채류, 과채류 유기종자에 우점하는 곰팡이와 세균에는 Altanaria sp.와 Pseudomonas sp.이 있었다. 2% 베이킹 소다 단독처리만으로는 근채류, 엽채류, 과채류 유기종자의 살균 효과가 낮았지만, 초음파와 혼합처리를 할 경우 발아율과 소독 효과가 상승하였다. 무, 순무, 배추 및 양배추 유기종자에서는 2% 베이킹 소다에서 초음파를 각각 1분간 처리하는 것이 살균 효과와 발아율에 가장 좋았다. 비트, 참외 및 수박 유기종자는 2% 베이킹 소다에서 초음파를 각각 2분간 처리하는 것이 살균 효과와 발아율에 가장 좋았다. 향후, 초음파와 베이킹 소다를 이용한 친환경 종자소독기술은 다른 기술보다 더 효과적이고 경제적이기 때문 다른 작물에 대한 확대 연구가 필요할 것으로 생각한다. The purpose of this study was to estimate the efficacy of 2% baking soda (sodium bicarbonate) and ultrasonication on the fungi and bacteria disinfection and germination of organic vegetable seeds. The predominant fungi and bacterium were Altanaria sp. and Pseudomonas sp. in organic vegetable seeds. The treatment of 2% baking soda alone showed low germination rate of organic root, leafy vegetable and cucurbit seeds, but the germination and disinfection efficacy was increased by the combined treatment with 2% baking soda and ultrasonication. Among the vegetable seeds, Radish, turnip, Chinese cabbage, and cabbage treated with 2% baking soda and ultrasonication for one minute had the highest disinfection and germination efficacy. Also, beet, melon and watermelon were the highest disinfection and germination efficiency for 2 minutes of the combined treatment with 2% baking soda and ultrasonication. In the future, the ecofriendly seed disinfection technology using ultrasonication and baking soda is more effective and economical methods, so we need to expand research on other organic crops. KCI Citation Count: 1